2004
DOI: 10.1111/j.1460-9568.2004.03526.x
|View full text |Cite
|
Sign up to set email alerts
|

Reward expectation, orientation of attention and locus coeruleus‐medial frontal cortex interplay during learning

Abstract: Regulation of attention and promotion of behavioural flexibility are functions attributed to both the noradrenergic nucleus locus coeruleus (LC) and the prefrontal cortex (PFC). The PFC receives a large innervation from LC and small changes in catecholaminergic activity in PFC profoundly affect cognitive function. It is crucial to the understanding of learning-related plasticity, that the cognitive context driving LC neurons be determined and the relation to activity in PFC be elucidated. To this end simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
279
4
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(324 citation statements)
references
References 45 publications
35
279
4
6
Order By: Relevance
“…This account is consonant with Bouret and Sara's (2005) view of NE as a neural interrupt signal that promotes learning (see also Bouret & Sara, 2004;David Johnson, 2003): "… these [LC] neurons are activated within behavioral contexts that require a cognitive shift -that is, interruption of ongoing behavior and adaptation. This LC activation occurs whenever there is a change in environmental imperative, such as the appearance of a novel, unexpected event, or a change in stimulus-reinforcement contingencies within a formal learning situation.…”
Section: ) the Relationship Between The P3 And Learningmentioning
confidence: 69%
See 1 more Smart Citation
“…This account is consonant with Bouret and Sara's (2005) view of NE as a neural interrupt signal that promotes learning (see also Bouret & Sara, 2004;David Johnson, 2003): "… these [LC] neurons are activated within behavioral contexts that require a cognitive shift -that is, interruption of ongoing behavior and adaptation. This LC activation occurs whenever there is a change in environmental imperative, such as the appearance of a novel, unexpected event, or a change in stimulus-reinforcement contingencies within a formal learning situation.…”
Section: ) the Relationship Between The P3 And Learningmentioning
confidence: 69%
“…It has been shown that, when applied in a temporally strategic manner (e.g., when driven by the identification and evaluation of motivationally relevant stimuli), increases in gain produce an increase in the signal-to-noise ratio of subsequent processing and a concomitant improvement in the efficiency and reliability of behavioral responses (Servan-Schreiber, Printz, & Cohen, 1990). Accordingly, it has been found that LC phasic activation reliably precedes and is temporally linked to behavioral responses to attended stimuli (Bouret & Sara, 2004;Clayton, Rajkowski, Cohen, & Aston-Jones, 2004). The idea that the LC may serve as a temporal filterfacilitating responses to task-relevant information at the moment that such information is being actively represented-is a key component of the adaptive gain theory , which posits an important role for the LC-NE system in optimizing task performance.…”
Section: ) Introductionmentioning
confidence: 99%
“…Manipulations similar to those used here increased norepinephrine release in the hippocampus by 165% in the first microdialysis sample after locus ceruleus glutamate infusion. The pattern of a brief (Ͻ400 ms) en masse firing episode in the locus ceruleus mimics that described in awake rats (Bouret and Sara, 2004); however, the long postactivation silence is not normally observed in physiological recordings of phasic activity, which are characterized by brief (ϳ500 ms) postactivation silent periods. The rate of firing during the glutamate-elicited phasic episode is likely close to the maximal rates reported for these neurons (ϳ10 -15 Hz).…”
Section: Electrode Placements and Recordingmentioning
confidence: 87%
“…Thus, the attribution of salience to stimuli following learning suggests that conditioned stimuli are particularly capable of evoking noradrenergic responses. In fact, locus coeruleus neurons respond vigorously to changes in stimulus-reinforcement contingencies, and this neural response precedes changes in behavioral responses (Aston-Jones et al, 1997;Bouret and Sara, 2004;Sara and Segal, 1991). Furthermore, recording studies in freely moving rats have shown that locus coeruleus neurons fire in response to salient stimuli on the first few presentations even in the absence of the unconditioned stimulus, but the neural response declines when the stimulus no longer evokes a conditioned response (Bouret and Sara, 2004;Sara and Segal, 1991).…”
Section: Time In Chamber (Sec)mentioning
confidence: 99%
“…In fact, locus coeruleus neurons respond vigorously to changes in stimulus-reinforcement contingencies, and this neural response precedes changes in behavioral responses (Aston-Jones et al, 1997;Bouret and Sara, 2004;Sara and Segal, 1991). Furthermore, recording studies in freely moving rats have shown that locus coeruleus neurons fire in response to salient stimuli on the first few presentations even in the absence of the unconditioned stimulus, but the neural response declines when the stimulus no longer evokes a conditioned response (Bouret and Sara, 2004;Sara and Segal, 1991). Direct stimulation of locus coeruleus neurons facilitates memory retrieval (Devauges and Sara, 1991;Sara and Devauges, 1988), supporting the notion that stimulus-evoked norepinephrine release initiates memory retrieval.…”
Section: Time In Chamber (Sec)mentioning
confidence: 99%